2000
DOI: 10.1176/appi.ajp.157.2.248
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Psychiatric Conditions on Health-Related Quality of Life in Persons With HIV Infection

Abstract: Optimization of health-related quality of life is particularly important now that HIV is a chronic disease with the prospect of long-term survival. Comorbid psychiatric conditions may serve as markers for impaired functioning and well-being in persons with HIV. Inclusion of sufficient numbers of appropriately trained mental health professionals to identify and treat such conditions may reduce unnecessary utilization of other health services and improve health-related quality of life in persons with HIV infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
171
3
11

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(196 citation statements)
references
References 28 publications
11
171
3
11
Order By: Relevance
“…These items were developed by the HCSUS consortium (Sherbourne et al 2000;Bing et al 2001;Burnam et al 2001) based on the short form of the World Health Organization's Composite International Diagnostic Interview (CIDI-SF) (Kessler et al 1998). …”
Section: Participantsmentioning
confidence: 99%
“…These items were developed by the HCSUS consortium (Sherbourne et al 2000;Bing et al 2001;Burnam et al 2001) based on the short form of the World Health Organization's Composite International Diagnostic Interview (CIDI-SF) (Kessler et al 1998). …”
Section: Participantsmentioning
confidence: 99%
“…The current estimates may represent an underestimation as there is evidence that depression may be under diagnosed in the context of HIV medical care (Steven et al, 2003). Previous research has also shown that depression in patients with HIV/AIDS may be associated with disease progression (Cook et al, 2004), reduced compliance with antiretroviral treatment (Rabkin et al, 2002), and as a result of additional illness burden, lead to a reduction in the quality of life (Sherbourne et al, 2000). Depressed individuals with HIV use significantly more health care and related services (Williams et al, 2005).…”
Section: Depressive Disorder In Patients With Hiv/aidsmentioning
confidence: 99%
“…We know from studies of patients and general populations that mood disorders, particularly depression, have a substantial negative impact on a person's health-related quality of life (Jia et al, 2004). In fact, for most domains of functioning and well-being, depression is more debilitating than most medical conditions (Sherbourne et al, 2000). In a study conducted by Sherbourne et al (2000) to assess the impact of psychiatric conditions on health related quality of life, they recruited a national probability sample of persons with HIV, receiving medical care in the United States.…”
Section: Consequences Of Neuropsychiatric Problems In Patients With Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that a person's ability to cope with HIV infection can be influenced by a multitude of psychosocial variables, including depression and quality of life (Ciesla and Roberts 2001;Grassi et al 1998;Sherbourne et al 2000). Depression is a common co-morbidity in patients with HIV infection.…”
mentioning
confidence: 99%